Minat Wirausaha Mahasiswa Berbasis Ekonomi Kreatif di Masa Pandemi Covid 19 - Dwi Rorin Mauludin Insana; Imam Suseno; Yolanda Yolanda (Sosio e-Kons, 2022)
The ongoing COVID-19 pandemic has had a profound impact on the economy. This study is intended to determine the potential and interest of students for creative economy-based entrepreneurship in the midst of the COVID-19 pandemic situation. This study uses a descriptive qualitative research approach. The analysis was carried out in stages, namely the data reduction stage, then presented the data qualitatively, and verified the research data information. The results of the research show that there are several reasons respondents are interested in owning a business, namely wanting to have a side business in addition to their existing job, wanting to have their own income, wanting to help the family economy, wanting to develop their potential and helping provide jobs for others, wanting to be free and not bound by time. work, want to be financially free. Meanwhile, the businesses that respondents are interested in during this pandemic are creative economy-based businesses, including online businesses (digitalpreneurs), culinary businesses, fashion businesses, handicrafts, printing, content creators, health product businesses, especially herbal ingredients and medical devices related to pandemic covid 19 (hand sanitizers, masks, disinfectants, hand soap), educational services and grocery stores. Pandemi covid-19 yang masih berlangsung hingga saat ini sangat berdampak terhadap aspek ekonomi. Penelitian ini dimaksudkan untuk mengetahui potensi dan keminatan mahasiswa untuk berwirausaha berbasis ekonomi kreatif ditengah situasi pandemic covid-19. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif. Analisis dilaksanakan secara bertahap yaitu tahap reduksi data, kemudian menyajikan data secara kualitatif, dan melakukan verifikasi terhadap informasi data penelitian. Hasil penelittian menunjukan beberapa alasan responden berminat untuk memiliki usaha yaitu ingin punya usaha sampingan selain pekerjaan yang sudah ada, ingin punya pendapatan sendiri, ingin membantu perekonomian keluarga, ingin mengembangkan potensi diri dan membantu menyediakan lapangan pekerjaan buat orang lain, ingin bebas dan tidak terikat waktu kerja, ingin bebas secara keuangan. Sedangkan usaha yang diminati oleh responden di masa pandemic ini adalah usaha berbasis ekonomi kreatif, antara lain bisnis online (digitalpreneur), usaha kuliner, usaha fashion, kerajinan tangan, percetakan, konten creator, usaha produk kesehatan terutama ramuan herbal dan alat kesehatan yang berhubungan dengan pandemic covid 19 (hand sanitizer, masker, desinfektan, sabun cuci tangan), jasa pendidikan dan toko kelontongan.